Mental Health Outcomes and Associations During the COVID-19 Pandemic: A Cross-Sectional Population-Based Study in the United States - Kantor, Bella Nichole; Kantor, Jonathan (Frontiers in Psychiatry, 2020)
COVID-19 may lead to significant mental health stresses, potentially with modifiable risk factors. We performed an internet-based cross-sectional survey of an age-, sex-, and race- stratified representative sample from the US general population. Degrees of anxiety, depression, and loneliness were assessed using the 7-item Generalized Anxiety Disorder scale (GAD-7), the 9-item Patient Health Questionnaire (PHQ-9), and the 8-item UCLA Loneliness Scale, respectively. Unadjusted and multivariable logistic regression analyses were performed to determine associations with baseline demographic characteristics. A total of 1,005 finished surveys were returned of the 1,020 started, yielding a completion rate of 98.5% in the survey panel. The mean (SD) age of respondents was 45 (16), and 494 (48.8%) were male. Overall, 264 subjects (26.8%) met criteria for an anxiety disorder based on a GAD-7 cutoff of 10; a cutoff of 7 yielded 416 subjects (41.4%) meeting clinical criteria for anxiety. On multivariable analysis, male sex (OR 0.65, 95% CI [0.49, 0.87]), identification as Black (OR 0.49, 95% CI [0.31, 0.77]), and living in a larger home (OR 0.46, 95% CI [0.24, 0.88]) were associated with a decreased odds of meeting anxiety criteria. Rural location (OR 1.39, 95% CI [1.03, 1.89]), loneliness (OR 4.92, 95% CI [3.18, 7.62]), and history of hospitalization (OR 2.04, 95% CI [1.38, 3.03]), were associated with increased odds of meeting anxiety criteria. 232 subjects (23.6%) met criteria for clinical depression. On multivariable analysis, male sex (OR 0.71, 95% CI [0.53, 0.95]), identifying as Black (OR 0.62, 95% CI [0.40, 0.97]), increased time outdoors (OR 0.51, 95% CI [0.29, 0.92]), and living in a larger home (OR 0.35, 95% CI [0.18, 0.69]), were associated with decreased odds of meeting depression criteria. Having lost a job (OR 1.64, 95% CI [1.05, 2.54]), loneliness (OR 10.42, 95% CI [6.26, 17.36]), and history of hospitalization (OR 2.42, 95% CI [1.62, 3.62]), were associated with an increased odds of meeting depression criteria. Income, media consumption, and religiosity were not associated with mental health outcomes. Anxiety and depression are common in the US general population in the context of the COVID-19 pandemic, and are associated with potentially modifiable factors.